Exceptional CO2 working capacity in a heterodiamine-grafted metal-organic framework - Lee, Woo Ram; Jo, Hyuna; Yang, Li-Ming; Lee, Hanyeong; Ryu, Dae Won; Lim, Kwang Soo; Song, Jeong Hwa; Min, Da Young; Han, Sang Soo; Seo, Jeong Gil; Park, Yong Ki; Moon, Dohyun; et al. (ROYAL SOC CHEMISTRY, 2015)
An amine-functionalized metal-organic framework (MOF), dmen-Mg-2(dobpdc) (dmen = N, N-dimethylethylenediamine), which contains a heterodiamine with both primary and tertiary amines, was prepared via a post-synthetic method. This material exhibits a significant selectivity factor for CO2 over N-2 that is commensurate with top-performing MOFs. It is remarkable that the solid is fully regenerated under vacuum or flowing Ar at low desorption temperatures, and following this can take up CO2 at more than 13 wt%. An exceptionally high working capacity is achieved at low regeneration temperatures and after exposure to humid conditions, which are important parameters for a real post-combustion CO2 capture process.
Keywords: CARBON-DIOXIDE CAPTURE; FLUE-GAS; ADSORPTION; SEPARATION; POLYMER; AIR; SORPTION; SELECTIVITY; ADSORBENTS; STABILITY